2021
DOI: 10.3390/horticulturae7110500
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microbial Fertilizer on the Growth, Rhizospheric Environment and Medicinal Quality of Fritillaria taipaiensis

Abstract: Fritillaria taipaiensis is a valuable traditional Chinese medicinal plant affected by germplasm degradation during cultivation. To find a suitable solution for this problem, F. taipaiensis was inoculated with exogenous arbuscular mycorrhiza (AM) fungi, potassium-solubilizing bacteria, and phosphorus-solubilizing bacteria in pot experiments. The effects of inoculation on the AM colonization, photosynthetic pigment, and superoxide dismutase contents, rhizospheric enzyme activities, alkaloid, and nucleotide conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In the present study, microorganisms in the composite microbial fertilizer helped the soil maintain moderate moisture content and increased the water-holding capacity of the soil. They are able to decompose organic matter to release extracellular polysaccharides and form sticky substances that help to keep water available in the soil and reduce water evaporation and loss [24]. Soil particle size composition is one of the most important physical properties of soil, which has an important effect on soil moisture and fertility storage and is closely related to soil structural stability [25].…”
Section: Effect Of Chemical Fertilizer With Compound Microbial Fertil...mentioning
confidence: 99%
“…In the present study, microorganisms in the composite microbial fertilizer helped the soil maintain moderate moisture content and increased the water-holding capacity of the soil. They are able to decompose organic matter to release extracellular polysaccharides and form sticky substances that help to keep water available in the soil and reduce water evaporation and loss [24]. Soil particle size composition is one of the most important physical properties of soil, which has an important effect on soil moisture and fertility storage and is closely related to soil structural stability [25].…”
Section: Effect Of Chemical Fertilizer With Compound Microbial Fertil...mentioning
confidence: 99%
“…However, irrational fertilization can lead to a series of environmental problems, including soil biodiversity and productivity reduction ( Guo et al, 2010 ; Yang et al, 2018 ), environmental pollution ( Probert et al, 1998 ; Drijber et al, 2000 ), and soil acidification ( Ahmad et al, 2013 ; Xiao et al, 2021 ; Xie et al, 2021 ). At present, measures such as fallowing, organic substitution ( Dai et al, 2019 ; Ji et al, 2020 ; Zhang et al, 2021 ), green manure planting ( Zhang et al, 2017 ; Ma et al, 2021 ), and biofertilizer promotion ( Wu et al, 2005 ; Castro et al, 2020 ; Zhou et al, 2021 ) have been implemented in agriculture to reduce the detrimental impacts of fertilization. Biofertilizers have become a research hotspot because of their environmental friendliness and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al (2022) reported that the crude fat content was increased by 22.97% in Elymus nutans plant compared to control. It was reported that in China, MF have been widely used in the cultivation of some medicinal materials, which not only improve the structure of soil, but also promote the quality and yield of medicinal materials (Zhou et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%